Methodological characteristics of sustainability science: a systematic review (2017)
Sustainability science has emerged as a research program and a scientific trend that directs all efforts to promote transition of societies toward sustainability. The style of research proposed to tackle unsustainability issues should be characterized by the application of a systems approach, as well as transdisciplinarity, participation, generation of social learning and a problem-solving perspective. However, whether such traits are being actually implemented has not been determined. Furthermore, a mature science is expected to have coherent research typologies, besides a scientific community and shared theoretical assumptions and methodological prescriptions; such types or research on sustainability science is still unknown. This systematic review aimed at analyzing research papers on sustainability carried out in 2013. Three aspects were studied: the scientific community, the theoretical assumptions on the concept of sustainability and the methodological design. Results suggest that the scientific community comes from disciplines different to sustainability, the researchers tend not to define the concept of sustainability and among those who do, and there is a lack of shared assumptions. The present analysis also showed that research on sustainability has not implemented the methodological characteristics mentioned and coherent method typologies were not found. These aspects hinder sustainability science evolution and maturity, given the difficulty to construct theories and consolidate a scientific community that develops coherent methods on such grounds.